Article on Impact of Good Governance on School Performance of Nepal - Nepal, Bimal (Journal of Research and Development, 2022)
This article deals with the impact of good governance on school performance in Nepal. Good governance and its impacts on school performance is a burning as well as searching issue in the field of the educational sector of Nepal. The purpose is to explore and to discuss the findings of the impact of good governance on school performance through critical analysis of the literature review. This article is based entirely on the secondary sources. The finding of the study is that the good governance practices play the significant role in school performance in Nepal. Further, other major findings of this review include low school performance, less participation of stakeholders, lack of transparency and accountability, and corruption in the education sector. The reason for the low performance of schools in Nepal is the lack of good governance. If we adopt good governance practice in education, we can easily ensure/achieve a better school; better performance is the implications of this literature review.